Epistemic parenthetical constructions on constructional perspective - Leite Goncalves, Sebastiao Carlos [UNESP] (Univ Federal Fluminense, 2015)
In this paper, I investigate epistemic parenthetical constructions originated from a constructional scheme formed by a matrix clause with adjectival epistemic predicator and an embedded clause in subject position. I assume the theoretical and methodological framework of Cognitive-Functional Linguistics (CROFT, 2001; TRAUGOTT, 2008). Based on spoken and writing language data of contemporary Brazilian Portuguese, I show that the matrix constructions which become grammaticalized function as focusing and asseverative epistemic parenthetical constructions. The identification of schematicity levels of the constructions, while it allows inferring a diachronic process of constructional change, it provides clues to the formation of a broader explanatory framework about the formation and functioning of epistemic parenthetical constructions.
Keywords: constructionalization; epistemic parenthetical constructions; subjective clauses